Patients' and procedural characteristics of AV-block during slow pathway modulation for AVNRT-single center 10 year experience. (1st October 2017) - Wasmer, Kristina; Dechering, Dirk G.; Köbe, Julia; Leitz, Patrick; Frommeyer, Gerrit; Lange, Phillip S.; Kochhäuser, Simon; Reinke, Florian; Pott, Christian; Mönnig, Gerold; Breithardt, Günter; Eckardt, Lars
Abstract: Background: Permanent AV-block is a recognized and feared complication of slow pathway modulation for AVNRT. We aimed to assess incidence of transient and permanent AV-block as well as consequences of transient AV-block in a large contemporary AVNRT ablation cohort. Methods: We searched our single center prospective ablation database for occurrence of transient and permanent AV-block during slow pathway modulation between January 2004 and October 2015. We analyzed patients' and procedural characteristics as well as outcome of patients in whom transient or permanent AV-block occurred. Results: Of 9170 patients who underwent a catheter ablation at our institution between January 2004 and October 2015, 2101 patients (64% women, mean age 50 ± 18 years) underwent slow pathway modulation. In three patients, permanent AV-block occurred during RF application. Additional two patients had transient AV-block that recovered (after a few minutes and 25 min), but recurred within two days of the procedure. All five patients underwent dual chamber pacemaker implantation (0.2%). Transient AV-block related to RF delivery occurred in 44 patients (2%). Transient mechanical AV-block occurred in additional 17 patients (0.8%). In 12 patients, ablation was continued despite transient AV-block. One of these patients developed permanent AV-block. Conclusion: Permanent AV-block following slow pathway modulation is a rare event, occurring in 0.2% of patients in a large contemporary single center cohort. Transient AV-block is more frequent (2%).